Analysis of the movement pattern of overburden and the form of spatial development of separation after mining in a fully mechanized caving face - Huang, Wanpeng; Yang, Mingfeng; Liu, Yaxin; Sui, Le; Gao, Mingtao; Wang, Xiao; Gao, Haibin (Frontiers in Earth Science, 2023)
For the fully mechanized caving face, it is easy to cause significant surface subsidence and other related problems after large-scale mining of coal seams, we should take some measures to solve them. In this study, in order to further explore the movement pattern of overburden and the form of spatial development of separation after mining in a fully mechanized caving face, we combined the engineering practice of Tangshan mining area, took the T2294 and T2291 working faces as the engineering background and used the three methods of similar simulation, numerical simulation and field measurement to comprehensively study. The results show that in the first stage of working face mining, the separation can generally reach 0.31 times the mining thickness of the coal seam, and the maximum can reach 0.58 times the mining thickness; in the second stage, the width of the separation seam is narrow, and the separation is small. It generally takes 20~30 days for the separation to reach its maximum from initiation, which is equivalent to the working face advancing 70~100 m, and the corresponding horizon height is 200 m. The research results provide theoretical guidance and a basis of engineering practice for the safe mining of multiple working faces under the Jingshan railway. This study even provides a basic theoretical reference for the safe mining of a thick coal seam working face under similar engineering geological conditions.